Syringaldehyde Alleviates Cardiac Hypertrophy Induced by Hyperglycemia in H9c2 Cells Through GLP-1 Receptor Signals - Li, Yingxiao; Hsu, Chao-Tien; Yang, Ting-Ting; Cheng, Kai-Chun (Pharmaceuticals (Basel, Switzerland), 2025)
Background: Cardiac hypertrophy is a significant complication of diabetes, often triggered by hyperglycemia. Glucagon-like peptide-1 (GLP-1) receptor agonists alleviate cardiac hypertrophy, but their efficacy diminishes under GLP-1 resistance. Syringaldehyde (SA), a natural phenolic compound, may activate GLP-1 receptors and mitigate hypertrophy. This study explores SA’s therapeutic potential in hyperglycemia-induced cardiac hypertrophy in H9c2 cardiomyocytes. Methods: H9c2 cells were exposed to high glucose to induce hypertrophy. Cells were treated with varying SA concentrations, and hypertrophic biomarkers were analyzed using ELISA, qPCR, and Western blot. Results: SA reduced cell size and hypertrophic biomarkers in a dose-dependent manner while increasing GLP-1 receptor expression and cAMP levels. These effects were attenuated in GLP-1-resistant cells, highlighting the role of GLP-1 receptor activation. AMPK activation was essential, as its inhibition abolished SA’s effects. SA also decreased O-linked N-acetylglucosamine transferase (OGT) expression via AMPK activation, contributing to reduced hypertrophy. Conclusions: SA alleviates hyperglycemia-induced cardiac hypertrophy in H9c2 cells by activating the GLP-1 receptor and AMPK signaling pathway.